Data structures and algorithms in C++ - Drozdek, Adam (Boston, MA : Cengage Learning, 2013)
This authoritative guide demystifies even the most difficult mathematical concepts so that you can gain a clear understanding of data structures and algorithms in C++. The authors incorporate the object-oriented design paradigm using C++ as the implementation language, while also providing intuition and analysis of fundamental algorithms. This book offers a unique multimedia format for learning the fundamentals of data structures and algorithms. Featuring a clear, easy-to-understand writing style that breaks down even the most difficult mathematical concepts.
Includes bibliographical references and index.
Keywords: C++ (Computer program language; Data structures (Computer science).; Computer algorithms